Autonomy and factors affecting dental health care seeking behaviour in women: An application of theory of planned behaviour - B.K. Aparna; R. Yashoda; Manjunath P. Puranik (Elsevier, 2024)
Background: Understanding oral health care seeking behaviour and it's determinants is essential in improving oral health. The health care utilization in women was found to be influenced by their autonomy. A socio-cognitive model that can explain variance in dental attendance behaviour in women including autonomy has yet to be validated. The Theory of Planned Behaviour (TPB), which takes into account women's autonomy, attitude, subjective norms, and perceived behavioural control, is empirically tested in this study with regard to self-reported dental visiting intentions and dental health seeking behaviour. Method: Cross sectional study using self-administered questionnaires was conducted to assess socio-demographic factors, autonomy, dental visiting behaviors as well as constructs of TPB model in 400 women aged 18 years or older in Bangalore city selected via stratified cluster sampling method. Two-stage structural equation modelling (SEM) was used to test the hypothesized TPB model. Results: The proposed correlated 5-factor measurement model was confirmed through confirmatory factor analysis (CFA). In SEM subjective norm (β = 0.17), perceived behavioural control (β = −0.27) and autonomy (β = 0.49) significantly predicted dental visiting intentions in women. Intention (β = 0.56) and autonomy (β = 0.25) explained dental visiting behaviour. It also revealed indirect effect of autonomy and perceived behaviour control on dental visiting behaviour through intentions. The hypothesized model predicted 27.6 % and 23.8% of the variance in intention and dental visiting behaviour respectively. Conclusion: The hypothesized model was successful in predicting intention and dental visiting behaviour in women. This could explain the multidimensional nature of dental care utilization in women which in turn might be helpful in improving access to dental care among them in future.